Modèles de firme et formes du capitalisme : Penser la diversité comme agenda de recherche pour la TR - Yannick Lung (Revue de la Régulation)
The paper proposes to focus the research agenda of the régulation theory on the synchronic diversity of institutional forms articulating different levels of analysis (micro, meso, macro). Part 1 concerns relationships between institution and organization, discussing the isomorphism hypothesis and underlying coupling micro / macro approaches of the diversity of institutional forms. Part 2 discusses the multi-level interactions between firms, industries and social system of innovation and production